Comparative Analysis of Filler Wall Interlock System Using Three Different Wall Material Using ETABS - Sandeep Kumar Gupta; Pradeep Kumar Nimal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
A reinforced concrete building with masonry infill is most common type of construction in India. Traditionally, conventional clay bricks or concrete blocks which are heavy rigid materials have been used as Infill wall. Though, AAC (aerated light weight concrete) blocks which are lightweight, flexible building materials that provides insulation and fire resistance and have lower impact on environment, can be used as masonry infill (MI) material in buildings. AAC blocks are now also available in India. A number of researchers have studied the behavior of AAC in-filled reinforced concrete (R/C) frames experimentally. Interlocking Bricks are even introduced further which adds an advantage over AAC bricks.Hence in the report, comparative study of the effect of type of infill wall material on wind response of structure has been presented. AAC blocks, Interlocking Blocks and conventional clay bricks materials are used for the comparison. To check the behavior of RC frames with interlocking blocks, AAC block and conventional clay bricks infill, analysis has been done using ETABS. Three models are considered for comparison. One is infill with conventional bricks, 2nd is infill with AAC blocks and third is infill frame with open ground storey. To model the infill analytically, equivalent diagonal strut method is used. The ends of diagonal strut are pin jointed. Infill behaves like compression strut between column and beam and compression forces are transferred from one node to another. The analysis has been carried out for dead load (DL) live load (LL), and wind load. The results have shown that AAC block infill and interlocking blocks material behaves better under lateral loading than conventional brick. The study of the effect of types of infill materials used on the performance of RC infilled frames is still limited.
Keywords: Interlocking Blocks; AAC Block; Infill Frame; Equivalent Strut Model